Multisectoral Collaborative Extension Education on Social Reintegration of Children in Conflict with the Law - Wahyuni, Surita Triya; Kartika, Tuti; Aribowo (GoAcademica Research & Publishing, 2025)
This study addresses the social reintegration challenges faced by Children in Conflict with the Law (CICL), who often experience stigma, discrimination, and rejection post-rehabilitation. Existing legal education efforts have proven insufficient, prompting the development of a Collaborative Counseling Model using a Participatory Action Research (PAR) approach in Ciandam Village, Cianjur Regency. Twelve purposively selected participants, including stakeholders from government offices and the correctional center, were involved. Data were collected through interviews, focus group discussions, observation, and documentation, and analyzed using Miles and Huberman’s model with NVivo 15 support. A Community Working Team (TKM) was formed to implement the model, which included area mapping, home visits, and reassessment of CICL and their families. Counseling materials were delivered using infographic-based media and disseminated through community religious activities. Results showed significant improvement in public knowledge and attitudes, contributing to reduced stigma and enhanced reintegration. The model proved effective, replicable, and adaptable for broader use. The study recommends creating support forums for CICL parents and further research into model scalability.